The Interplay of Halal Operations Management and Supply Chain Integration on Logistics Performance in West Java's SMEs - Tribowo Rachmat Fauzan; Ajeung Syilva Syara Noor Silmi Sudrajat (Yayasan Kawanad, 2026)
The global expansion of the halal industry has placed considerable pressure on food supply chains, particularly among small and medium enterprises (SMEs) in West Java's food sector. This research examines the interplay between halal operations management practices and supply chain integration to determine their combined effects on logistics performance, addressing persistent gaps in halal logistics efficiency. A quantitative approach employing partial least squares structural equation modeling (PLS-SEM) analyzes survey responses from 186 food SMEs across West Java, treating halal operations management and supply chain integration as key independent constructs, with logistics performance as the dependent variable; mediation effects were tested through bootstrapping procedures. Halal operations management significantly improves logistics performance, while supply chain integration fully mediates this relationship — West Java SMEs show measurable gains in on-time delivery and inventory efficiency when halal practices are structurally aligned with supply chain coordination. The cross-sectional design limits causal inference, and findings may not generalize beyond food SMEs in West Java; future research should examine longitudinal effects and multi-sector applications across Indonesia. This study is among the first to connect halal operations management with supply chain integration in explaining logistics performance among Indonesian SMEs, addressing theoretical gaps between Islamic business practices and modern supply chain theory while offering a practical framework for West Java's halal sector development.